If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -15 = 2x + 55 Reorder the terms: -15 + 12x = 2x + 55 Reorder the terms: -15 + 12x = 55 + 2x Solving -15 + 12x = 55 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + 12x + -2x = 55 + 2x + -2x Combine like terms: 12x + -2x = 10x -15 + 10x = 55 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + 10x = 55 + 0 -15 + 10x = 55 Add '15' to each side of the equation. -15 + 15 + 10x = 55 + 15 Combine like terms: -15 + 15 = 0 0 + 10x = 55 + 15 10x = 55 + 15 Combine like terms: 55 + 15 = 70 10x = 70 Divide each side by '10'. x = 7 Simplifying x = 7
| 0.5(4x-22)=-25 | | 13x+21=15x+7 | | x^2+10xy+16y^2= | | 7x-8=5x | | 2y-2=0 | | 3w^2-24w^2+36=0 | | 8x^2+72x^2+64x= | | t^2-14t+49=0 | | 7x-3-2x=8+4 | | 4x^2-27x+39=-3x+4 | | (9x+15)(8x+15)=0 | | -x+10+5x=26 | | ((3x^2)-3)*((3x^2)-3)=0 | | x^7-256x^2= | | x^2+3x=2x+2 | | -3+-x+3x=-25 | | x^8-x^4= | | x^2-12x+36=9 | | 8x^3+4x^2-y^2-y^3=0 | | x^2+x-2= | | 8(3x+10)=28x(-14)-4x | | 12x+4y=80 | | x^7-256x^3= | | x^2-x-12=2x-2 | | x^2-x-10=10 | | 12x-7=11(x+9)-1 | | 10x-5=9(x+7)+10 | | 4t^2-19t-30=0 | | 3(x-12)-5=16x-93 | | 6x+0.2=4x-0.8 | | 11(x-9)-10=32x-298 | | 6x+0.2=4x-(-0.8) |